Induction of ornithine decarboxylase in guinea-pig lymphocytes and its relation to phospholipid metabolism - Otani, Shuzo; Matsui, Isao; Kuramoto, Ayako; Morisawa, Seiji (Biochimica et Biophysica Acta (BBA) - General Subjects, 1984)
Treatment of lymphocytes with exogenous phospholipase C (phosphatidylcholine cholinephosphohydrolase, EC 3.1.4.3.) derived from Clostridium perfringens at concentrations similar to those which induced ornithine decarboxylase ( L-ornithine carboxy-lyase, EC 4.1.1.17) activity produced diacylglycerol and phosphatidate. A divalent cation ionophore, A23187, and phytohemagglutinin induced not only diacylglycerol formation, but also ornithine decarboxylase activity. Dibutyryl cAMP inhibited both diacylglycerol formation and ornithine decarboxylase induction to a similar extent in phytohemagglutinin-stimulated lymphocytes, but stimulated them somewhat in ionophore A23187-activated lymphocytes. This suggests that the activation of intracellular phospholipase C and the formation of diacylglycerol is involved in ornithine decarboxylase induction in lymphocytes.